KODE-KODE BUDAYA DALAM FABEL MASYARAKAT ACEH - Yulsafli Yulsafli (Jurnal Metamorfosa, 2020)
This study is entitled "Cultural Code in the Aceh Community Fable". The formulation of the problem in this research is how is the cultural code in the Acehnese fable? To describe the cultural code in the Acehnese fable. The benefit of this research for the researchers themselves is that they can add insight into the literary codes contained in the Acehnese fable and as an input in studying and studying literature, especially fables. Sources of research data are the Acehnese fable, namely (1) Shearing Abang Gajah (Gayo), and (2) Carito Sang Nago Jo Tuanku Tapa (Jamee), (3) Origin of Monkeys (Simeulue), and (4) White Buffalo (Buffalo) ( Simeulue), and (5) Palandok (The Mouse Deer). The method used in this research is descriptive method. The data collection technique used in this study is the documentation technique. The data in this study were obtained from the book Collection of Oral Literature by Budiman Sulaiman in the 2000 issue. Based on the data processing and analysis, it was concluded that in the five fables analyzed there were various cultural codes, namely icons, symbols and indexes. An icon is a physical object (two or three dimensions) that resembles what it represents, a symbol is something or a condition that leads the subject's understanding of the object, while an index is a sign that is present sociatively due to the presence of a fixed characteristic reference relationship. Cultural codes in the Acehnese fable are very important, especially in shaping the character of children. Abstrak Penelitian ini bertujuan untuk mendeskripsikan kode budaya dalam masyarakat Aceh. Metode yang digunakan dalam penelitian ini adalah metode deskriptif.Teknik pengumpulan data yang dilakukan dalam penelitian ini adalah teknik dokumentasi.Data penelitian ini bersumber dari buku Kumpulan Fabel Masyarakat Acehyang ditulis oleh Budiman Sulaiman. Fabel yang dipilih berjumlah lima judul yang terdapat di Aceh, yaitu (1) Geser Geser Abang Gajah (Gayo), dan (2) Carito Sang Nago Jo Tuanku Tapa (Jamee), (3) Asal Mula Monyet (Simeulue), dan (4) Kerbau Putih (Simeulue), dan (5) Palandok (Si Kancil).Berdasarkan pengolahan dan analisis data diperoleh simpulan bahwa dalam dalam kelima fabel yang dianalisis tersebut terdapat bermacam-macam kode budaya, yaitu ikon, simbol, dan indeks.Ikon adalah sesuatu benda fisik yang menyerupai apa yang dipresentasikannya, simbol adalah sesuatu hal atau keadaan yang memimpin pemahaman si subjek kepada objek, sedangkan indeks adalah tanda yang hadir secara asosiatif akibat terdapatnya hubungan ciri acuan yang sifatnya tetap.Kode budaya dalam fabel masyarakat Aceh sangat bermanfaat dalam membentuk karakter anak baik sebagai individu, sebagai warga masyarakat, dan sebagai warga negara yang baik. Kata Kunci : Kode, Budaya, Fabel